Análise do pacto de non cedendo de crédito pecuniário à luz dos princípios contratuais - Duarte Filho, Marco Antonio Savazzo (2024)
Considering that credit rights are important for the promotion and economic development of companies and that, for some, such rights encompass the person's assets, this study aims to analyze aspects of validity of the pecuniary non ceding pact, provided for in art. 286 of the Civil Code. The convention prohibiting the assignment of credit rights is a clause commonly found in contracts, which can be considered, in many cases, as a style clause. In view of this, its insertion in contracts is not preceded by an economic-legal analysis, being, in general, imposed by the debtor, when there is an imbalance of forces. In this context, the purpose of the present work is, firstly, analyze the fundamental principles of contracts, in order to find out in which cases there is compatibility of the pact of non ceding in contracts. In the second part of the study, there is the development of the characteristics, legal nature and requirements for the validity of the agreement of the parties to prohibit the assignment of credit. In addition, foreign legislation on the pecuniary non ceding pact and the legislative evolution in Brazil regarding the limitation of agreeing such pact is presented. After the development of the work, the final considerations seek to identify if there are casuistic situations in which it should restrict, with regard to the pact of non ceding pecuniary, private autonomy